2013
DOI: 10.1111/ped.12089
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in children treated with restrictive diet for inherited metabolic disease

Abstract: As negative effects of the disease increased, the QoL of IMD patients and their parents decreased in terms of emotional, physical, and cognitive function. Application of expanded newborn scanning programs, early diagnosis, regular follow up, and family education would lessen the effects of the disease and improve the QoL of both families and children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 18 publications
2
28
1
Order By: Relevance
“…From six articles, only subgroup data were extracted. In four studies, we selected IT-IEM patients from the original samples, which integrated patients with IT-IEM and patients with other diseases [19,2123]. One study reported on IT-IEM patients before and after transplantation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From six articles, only subgroup data were extracted. In four studies, we selected IT-IEM patients from the original samples, which integrated patients with IT-IEM and patients with other diseases [19,2123]. One study reported on IT-IEM patients before and after transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…higher compared to Morbus Fabry and pharmacologically treated patients in most domains (no sign. group difference for social and environmental domains)Eminoglu et al, 2013 (Turkey) [23]MA, PA, MSUD (group includes n = 3 patients with a disease not being an IT-IEM) 14 Reviewed sample: separately reported subgroup, mainly IT-IEM, 3 other IEM Orig. sample: IT-IEM mixed with other IEM (N = 68)4.7 (n.a., SD = 4.3)Population norms, other IEM-groups: CMD and AMD• Questionnaire constructed by authors: QoL Scale for Metabolic Diseases (proxy-parent) • HrQoL (QoL Scale for Metabolic Diseases): Sign.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In countries other than Japan, some studies have been conducted on the daily life and QoL of patients with IEM and of their parents (Lambert and Boneh 2004;Simon et al 2008;Stockler et al 2012;Cazzoria et al 2014). As one of the factors associated with their QoL, children with IEM in Turkey with bad diet compliance reportedly had lower scores in two aspects of QoL assessment: school labeling and perception of disease (Eminoglu et al 2013). However, only a few studies in Japan have been conducted and these focused mainly on the patients' and on their mothers' QoL (Kubo et al 2008;Okano et al 2013).…”
mentioning
confidence: 99%